2017
DOI: 10.1123/ijspp.2016-0402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training at 2100-m Altitude on Running Speed and Session Rating of Perceived Exertion at Different Intensities in Elite Middle-Distance Runners

Abstract: Purpose:To determine the effect of training at 2100-m natural altitude on running speed (RS) during training sessions over a range of intensities relevant to middle-distance running performance. Methods: In an observational study, 19 elite middle-distance runners (mean ± SD age 25 ± 5 y, VO 2 max, 71 ± 5 mL · kg -1 · min -1 ) completed either 4-6 wk of sea-level training (CON, n = 7) or a 4-to 5-wk natural altitude-training camp living at 2100 m and training at 1400-2700 m (ALT, n = 12) after a period of sea-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Indeed, data from both team sport and endurance athletes indicate higher session RPE values are reported when training at altitude, compared to sea-level. 23,26,27 Our findings are in accordance with previous research in Australian Football players which showed that with the addition of hypoxic exposure, external training loads may be reduced compared to sea-level for a similar, or enhanced running performance. 28 Interestingly, despite the final two games of the case study occurring at high altitude (1300 and 1800 m), the player recorded a higher overall distance and acceleration count compared to matches played in his home environment (Tables S1 and S2 of Supplementary material).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, data from both team sport and endurance athletes indicate higher session RPE values are reported when training at altitude, compared to sea-level. 23,26,27 Our findings are in accordance with previous research in Australian Football players which showed that with the addition of hypoxic exposure, external training loads may be reduced compared to sea-level for a similar, or enhanced running performance. 28 Interestingly, despite the final two games of the case study occurring at high altitude (1300 and 1800 m), the player recorded a higher overall distance and acceleration count compared to matches played in his home environment (Tables S1 and S2 of Supplementary material).…”
Section: Discussionsupporting
confidence: 91%
“…Our investigation further expands the current literature on altitude training in elite athletes in which studies are commonly characterised by the collection of data over multiple time periods 6 , with varying altitude exposures 28 and/or use of simulated hypoxia 11 , or in the absence of measures of changes in Hbmass [29][30][31][32][33] . Unlike a few previous studies ( 18,19 ) that have failed to find an increase in Hbmass in elite athletes, and contrary to speculations on whether elite athletes with already high Hbmass benefit from altitude training 20 , we found significant Hbmass increases in our group of world-class distance athletes.…”
Section: Discussionmentioning
confidence: 93%
“…Due to the unique physiological stress that is inflicted by altitude exposure, it is traditionally recommended that athletes initially reduce their training volume to allow for acclimation [42]. Furthermore, growth and development processes associated with adolescence may increase nutritional and sleep needs in a manner that nuances the recovery process.…”
Section: Discussionmentioning
confidence: 99%